(untitled) (Proceeding of International Conference on Islamic Economics, Islamic Banking, Zakah and Waqf, 2023)
Consumers knowledge of the country of origin of a product is widely considered to be an important influence on their behavior in selecting products. However, sometimes the perspective of considering product selection is also influenced by consumer ethnocentrism. This study aims to find the effect of world-mindedness on consumer ethnocentrism. The survey method was used in this study by using a questionnaire to 268 Muslim youth respondents. Data were analyzed using the Rasch Model and Regression Analysis. The study shows that around 0.74% of the younger generation of Muslims think very broadly and 1.12% think very differently. There are 3.73% of respondents tend to have the most extreme ethnocentrism. This study also confirms that world-mindedness has a negative and significant effect on consumer ethnocentrism (p <0.05).